PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME EDUKASI WORD GUESSING PADA PELAJARAN PKN DI KELAS IV SDN 13 BOLANGITANG TIMUR - Muhamad Fachrul Alfajri Pohontu; Samsi Pomalingo; Aina Nurdiyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The problem in this research is that there is still a lack of concrete learning media that teachers can use in the learning process. This research aims to design Word Guessing Learning Media in Elementary Schools, to increase students' interest and knowledge about the norms that apply in everyday life. Development research is a type of ADDIE model development research (R&D) through 5 stages of Analysis, Design, Development, Implementation, and Evaluation. This research produces a product in the form of concrete learning media based on the Word Gusesing educational game in elementary schools.